Nonaqueous electrolyte secondary battery

By attaching sulfonic acid compounds to the positive electrode active substance of the nonaqueous electrolyte secondary battery and using a negative electrode core with high compressive strength, the problem of degradation of circulation characteristics is solved, and high capacity and excellent circulation characteristics are achieved.

CN119731824APending Publication Date: 2025-03-28PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380060092.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-26
Filing Date
2023-07-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

While ensuring high capacity, it is difficult to improve the cycle characteristics, especially because the charge and discharge depth of the existing nonaqueous electrolyte secondary batteries increase and the cycle characteristics decrease due to the decrease of the reaction resistance.

Method used

By attaching a sulfonic acid compound to the surface of the lithium-containing transition metal composite oxide particles of the positive electrode active material, and using a negative electrode core with a compressive strength of 300 MPa or more on the negative electrode, the volume change of the negative electrode mixture layer is reduced, the conduction path is maintained, and the circulation characteristics are improved.

Benefits of technology

High capacity and excellent cycle characteristics are achieved, ensuring that the battery can maintain good performance when the charging and discharging depth increases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731824A_ABST
    Figure CN119731824A_ABST
Patent Text Reader

Abstract

In a non-aqueous electrolyte secondary battery (10) as an example of an embodiment, a positive electrode (11) includes a lithium-containing transition metal composite oxide and a sulfonic acid compound present on a particle surface of the composite oxide. The sulfonic acid compound is a compound represented by formula (I). The negative electrode (12) has a negative electrode core and a negative electrode mixture layer formed on the surface of the negative electrode core, and the 1% compressive strength of the negative electrode core is 300 MPa or more. In the formula, A is a group 1 or group 2 element, R is a hydrocarbon group, and n is 1 or 2. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art

[0002] Patent document 1 proposes that Li4Ti5O 12 An active material having a surface layer composed of a lithium sulfonate compound formed on the surface of lithium titanate particles as a main component. Patent Document 1 states that by using this active material in a negative electrode active material, a change in resistance of a battery before and after charge storage can be suppressed.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-6164 Summary of the invention

[0006] In non-aqueous electrolyte secondary batteries, it is an important issue to improve cycle characteristics while ensuring high capacity. The prior art including Patent Document 1 cannot fully address such issues, and there is still much room for improvement.

[0007] The non-aqueous electrolyte secondary battery disclosed in the present invention is characterized in that it comprises a positive electrode, a negative electrode and a non-aqueous electrolyte, the positive electrode comprises a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of particles of the composite oxide, the sulfonic acid compound is a compound represented by formula (I), the negative electrode comprises a negative electrode core and a negative electrode mixture layer formed on the surface of the negative electrode core, and the 1% compressive strength of the negative electrode core is greater than 300 MPa.

[0008]

[0009] In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.

[0010] The nonaqueous electrolyte secondary battery disclosed herein has a high capacity and excellent cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment.

[0012] Figure 2 This is a diagram showing the relationship between strain and stress when a tensile test is performed on a negative electrode core. DETAILED DESCRIPTION

[0013] The research results of the present inventors have made it clear that by making the sulfonic acid compound shown in the above formula (I) present on the particle surface of the lithium-containing transition metal composite oxide used as the positive electrode active material, a non-aqueous electrolyte secondary battery with high capacity and low resistance can be realized. It is believed that the reason is that the reaction resistance in the positive electrode is reduced by the function of the sulfonic acid compound, and the charge and discharge depth can be deepened. However, as the charge and discharge depth deepens due to the reduction of the reaction resistance, a new problem such as the reduction of the cycle characteristics of the non-aqueous electrolyte secondary battery is generated. In this way, when the sulfonic acid compound is applied to the particle surface of the lithium-containing transition metal composite oxide, the sulfonic acid compound specifically functions to reduce the reaction resistance in the positive electrode and deepens the charge and discharge depth, but it is difficult to realize a non-aqueous electrolyte secondary battery with high capacity and excellent cycle characteristics by only using the sulfonic acid compound for the positive electrode.

[0014] The inventors of the present invention have repeatedly studied and found that the main reason for the reduction in the above-mentioned cycle characteristics is that as the sulfonic acid compound is used in the positive electrode and the charge and discharge depth is deepened, the volume change of the negative electrode mixture layer during charge and discharge becomes larger. Specifically, as the charge and discharge depth becomes deeper, the volume change of lithium absorption and deintercalation in the negative electrode active material in the negative electrode mixture layer during charge and discharge increases, and the contact degree between the negative electrode active materials becomes weaker or the contact state disappears due to repeated charge and discharge. Therefore, it is believed that the negative electrode active material isolated from the conductive path in the negative electrode mixture layer increases, resulting in a reduction in cycle characteristics.

[0015] Therefore, the inventors of the present invention have repeatedly conducted further research, and have successfully ensured high capacity while improving cycle characteristics by using a lithium-containing transition metal composite oxide with a specific sulfonic acid compound attached to the particle surface as a positive electrode active material and using a negative electrode core with a 1% compressive strength of more than 300 MPa in the negative electrode. According to the non-aqueous electrolyte secondary battery disclosed in the present invention, even if the charge and discharge depth of the negative electrode is deepened as the sulfonic acid compound is used in the positive electrode, the volume change of the negative electrode mixture layer during charge and discharge can be suppressed to a small extent by the negative electrode core with high compressive strength. As a result, even if charge and discharge are repeated, the conduction path between the negative electrode active materials will not be lost, and it is believed that the cycle characteristics are improved.

[0016] Hereinafter, an example of an embodiment of the nonaqueous electrolyte secondary battery of the present disclosure will be described in detail with reference to the drawings. It should be noted that a configuration obtained by selectively combining the various configuration features of the multiple embodiments and modifications described below is included in the scope of the present disclosure.

[0017] Hereinafter, as a non-aqueous electrolyte secondary battery, a cylindrical battery in which a wound electrode body 14 is housed in an outer can 16 having a bottomed cylindrical shape is exemplified, but the outer shell of the battery is not limited to a cylindrical outer can. The non-aqueous electrolyte secondary battery disclosed herein may be, for example, a square battery having a square outer can, a coin-shaped battery having a coin-shaped outer can, or a bag-shaped battery having an outer shell composed of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body is not limited to a wound type, and may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator.

[0018] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte, and an outer can 16 for storing the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. In the following, for the convenience of explanation, the sealing body 17 side of the battery is regarded as the upper side, and the bottom side of the outer can 16 is regarded as the lower side.

[0019] The non-aqueous electrolyte has lithium ion conductivity and may be a liquid electrolyte (electrolyte) or a solid electrolyte.

[0020] Liquid electrolyte (electrolyte) comprises non-aqueous solvent and electrolyte salt dissolved in non-aqueous solvent. Non-aqueous solvents include, for example, esters, ethers, nitriles, amides, and mixed solvents of more than two of these. As an example of non-aqueous solvents, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and mixed solvents thereof can be cited. Non-aqueous solvents can also contain halogen substitution bodies (for example, fluoroethylene carbonate, etc.) in which at least a portion of hydrogen in these solvents is replaced by halogen atoms such as fluorine. Lithium salts such as LiPF6 are used in electrolyte salts.

[0021] As a solid electrolyte, for example, a solid or gel-like polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As an inorganic solid electrolyte, a well-known material in a fully solid lithium-ion secondary battery, etc. (for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a halogen-based solid electrolyte, etc.) can be used. The polymer electrolyte, for example, comprises a lithium salt and a matrix polymer, or comprises a non-aqueous solvent, a lithium salt and a matrix polymer. As a matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent and gels is used. As polymer materials, fluororesins, acrylic resins, polyether resins, etc. can be listed.

[0022] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked along the radial direction of the electrode body 14 by being spirally wound. The negative electrode 12 is formed to be one circle larger than the positive electrode 11 to prevent the precipitation of lithium. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0023] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.

[0024] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed in the outer can 16, in which a part of the side portion protrudes inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 by the groove portion 22 and the open end of the outer can 16 that is pressed and connected to the sealing body 17.

[0025] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.

[0026] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 will be described in detail.

[0027] [positive electrode]

[0028] The positive electrode 11 has a positive electrode core 30 and a positive electrode mixture layer 31 disposed on the surface of the positive electrode core 30. The positive electrode core 30 can use a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film of the metal disposed on the surface, etc. The positive electrode mixture layer 31 preferably contains a positive electrode active material, a conductive agent, and a binder, and is disposed on both sides of the positive electrode core 30 except for the portion to which the positive electrode lead 20 is connected. The positive electrode 11 can be manufactured, for example, by applying a positive electrode composite material slurry containing a positive electrode active material, a conductive agent, and a binder to the surface of the positive electrode core 30, drying the coating, and then compressing to form the positive electrode mixture layer 31 on both sides of the positive electrode core 30.

[0029] As the conductive agent contained in the positive electrode mixture layer 31, carbon black such as acetylene black and Ketjen black, graphite, carbon nanotubes (CNT), carbon nanofibers, graphene and other carbon materials can be exemplified. As the binder contained in the positive electrode mixture layer 31, fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. In addition, these resins can also be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide, etc. The content of the conductive agent and the binder is, for example, 0.1 to 5.0% by mass relative to the mass of the positive electrode mixture layer 31.

[0030] The positive electrode 11 includes a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles. The lithium-containing transition metal composite oxide with the sulfonic acid compound attached to the particle surface functions as a positive electrode active material. The sulfonic acid compound is a compound represented by formula (I).

[0031]

[0032] In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.

[0033] The sulfonic acid compound represented by formula (I) (hereinafter, sometimes referred to as "sulfonic acid compound") reduces the reaction resistance in the positive electrode 11 and improves the power characteristics of the battery. In addition, as the resistance is reduced, the charge and discharge depth can be deepened, and high capacity can be achieved. The sulfonic acid compound can exert this effect even in a very small amount, but it is preferably present on the particle surface of the composite oxide in an amount of 0.01% by mass or more relative to the mass of the lithium-containing transition metal composite oxide. The content of the sulfonic acid compound is more preferably 0.05% by mass or more, and particularly preferably 0.10% by mass or more relative to the mass of the lithium-containing transition metal composite oxide.

[0034] The upper limit of the content of the sulfonic acid compound is not particularly limited, but from the viewpoint of cycle characteristics, it is preferably 2.0% by mass, more preferably 1.5% by mass, and particularly preferably 1.0% by mass relative to the mass of the lithium-containing transition metal composite oxide. The sulfonic acid compound is present, for example, in an amount of 0.05 to 1.50% by mass or 0.1 to 1.0% by mass relative to the mass of the lithium-containing transition metal composite oxide.

[0035] The positive electrode active material has a lithium-containing transition metal composite oxide with a sulfonic acid compound attached to the particle surface, that is, a composite particle as a main component, or can be substantially composed of only the composite particle. It should be noted that, within the scope of not impairing the purpose of the present disclosure, the positive electrode active material may also contain a composite oxide or other compound other than the composite particle.

[0036] The lithium-containing transition metal oxide preferably has a layered rock salt structure. As the layered rock salt structure of the lithium-containing transition metal oxide, for example, a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, etc. can be cited. Among them, from the viewpoint of high capacity and stability of the crystal structure, a layered rock salt structure belonging to the space group R-3m is preferred. The layered rock salt structure of the lithium-containing transition metal oxide comprises a transition metal layer, a Li layer and an oxygen layer.

[0037] The lithium-containing transition metal oxide is a composite oxide containing metal elements such as Co, Mn, Ni, and Al in addition to Li. The metal element constituting the lithium-containing transition metal oxide is, for example, at least one selected from Mg, Al, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Y, Zr, Sn, Sb, W, Pb, and Bi. Among them, it is preferred to contain at least one selected from Co, Ni, and Mn. As an example of a suitable composite oxide, a composite oxide containing Ni, Co, and Mn and a composite oxide containing Ni, Co, and Al can be listed.

[0038] From the viewpoint of high capacity, the lithium-containing transition metal oxide preferably contains 70 mol% or more, more preferably 80 mol% or more of Ni relative to the total molar number of metal elements other than Li. In addition, the effect of adding the sulfonic acid compound is more significant when a lithium-containing transition metal oxide with a high Ni content is used. The Ni content relative to the total molar number of metal elements other than Li can be 85 mol% or more, or 90 mol% or more. The upper limit of the Ni content is, for example, 95 mol%.

[0039] As described above, an example of a suitable lithium-containing transition metal oxide is a composite oxide containing Ni, Co, and Al. Relative to the total molar number of metal elements other than Li, the content of Al is 4 to 15 mol%, and the content of Co is less than 1.5 mol%. If the content of Al is within this range, it helps to stabilize the crystal structure and improve the cycle characteristics. Co may not be substantially added, and the battery performance is improved by adding a small amount of Co.

[0040] For example, lithium-containing transition metal oxides are composed of the general formula Li a Ni x Al y Co z M1 w O 2-b (wherein, 0.8≤a≤1.2, 0.85≤x≤0.95, 0.04≤y≤0.15, 0≤z≤0.015, 0≤w≤0.15, 0≤b<0.05, x+y+z+w=1, M1 is at least one element selected from the group consisting of Mn, Fe, Ti, Si, Nb, Zr, Mo and Zn.) A composite oxide represented by M1 is preferably Mn.

[0041] The content of elements constituting the lithium-containing transition metal composite oxide can be measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.

[0042] The lithium-containing transition metal composite oxide is, for example, a secondary particle formed by the aggregation of multiple primary particles. The volume-based median particle size (D50) of the composite oxide is not particularly limited, and as an example, it is 3μm to 30μm, preferably 5μm to 25μm. In the case where the composite oxide is a secondary particle formed by the aggregation of primary particles, the D50 of the composite oxide refers to the D50 of the secondary particle. D50 refers to the particle size at which the cumulative frequency from the smaller particle size in the volume-based particle size distribution becomes 50%, also known as the median diameter. The particle size distribution of the composite oxide (the same is true for the negative electrode active material) can be measured using a laser diffraction particle size distribution measuring device (for example, Microtrac Bell Co., Inc., MT3000II) and water as the dispersion medium.

[0043] The average particle size of primary particles constituting the lithium-containing transition metal composite oxide is, for example, 0.05 μm to 1 μm. The average particle size of the primary particles is calculated by averaging the diameters of the circumscribed circles of the primary particles obtained by analyzing a scanning electron microscope (SEM) image of a cross section of secondary particles.

[0044] The sulfonic acid compound present on the surface of the particles of the lithium-containing transition metal composite oxide is a compound represented by formula (I) as described above.

[0045]

[0046] In the formula, A is an element of Group 1 or Group 2, R is a hydrocarbon group, and n is 1 or 2. A is preferably an element of Group 1. Among them, Li or Na is more preferred, and Li is particularly preferred.

[0047] In formula (I), R is preferably an alkyl group. The carbon number of the alkyl group is preferably 5 or less, and more preferably 3 or less. From the viewpoint of reducing the reaction resistance, an example of a suitable R is an alkyl group having a carbon number of 3 or less, wherein a methyl group is preferred. It should be noted that, in R, a portion of hydrogen bonded to carbon may also be substituted by fluorine. In addition, n in formula (I) is preferably 1.

[0048] Specific examples of the sulfonic acid compound include lithium methanesulfonate, lithium ethanesulfonate, lithium propanesulfonate, sodium methanesulfonate, sodium ethanesulfonate, magnesium methanesulfonate, lithium fluoromethanesulfonate, etc. Among them, at least one selected from the group consisting of lithium methanesulfonate, lithium ethanesulfonate and sodium methanesulfonate is preferred, and lithium methanesulfonate is particularly preferred.

[0049] The sulfonic acid compound is, for example, uniformly present on the entire surface of the particles of the lithium-containing transition metal composite oxide. The presence of the sulfonic acid compound on the surface of the particles of the lithium-containing transition metal composite oxide can be confirmed by Fourier transform infrared spectroscopy (FT-IR). In the infrared absorption spectrum obtained by FT-IR, the positive electrode active material containing lithium methanesulfonate, for example, has a peak at 1238 cm -1 、1175cm -1 、1065cm -1 、785cm -1 There is an absorption peak near 1238cm -1 、1175cm -1 、1065cm -1 The peaks near 785cm are caused by the SO stretching vibration of lithium methanesulfonate. -1 The nearby peaks are peaks derived from CS stretching vibration of lithium methanesulfonate.

[0050] For positive electrode active materials containing sulfonic acid compounds other than lithium methanesulfonate, the presence can also be confirmed by the absorption peak derived from the sulfonic acid compound in the infrared absorption spectrum. It should be noted that the presence of the sulfonic acid compound on the particle surface of the lithium-containing transition metal composite oxide can also be confirmed by ICP, atomic absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), radioactive light XRD measurement, TOF-SIMS, etc.

[0051] The positive electrode active material as an example of the embodiment can be produced by the following method. It should be noted that the production method described here is an example, and the production method of the positive electrode active material is not limited to this method.

[0052] First, a metal oxide containing metal elements such as Ni, Al, Co, and Mn is synthesized. Then, the metal oxide and a lithium compound are mixed and calcined to obtain a lithium-containing transition metal composite oxide. The metal oxide is synthesized, for example, by stirring a solution of a metal salt containing Ni, Al, Co, Mn, etc. while dropping an alkaline solution such as sodium hydroxide, adjusting the pH to the alkaline side (for example, 8.5 to 12.5), thereby precipitating (coprecipitating) a composite hydroxide containing metal elements such as Ni, Al, Co, and Mn, and heat-treating the composite hydroxide to enable synthesis. The heat treatment temperature is not particularly limited, and as an example, it is 300°C to 600°C.

[0053] Examples of lithium compounds include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. The metal oxide and the lithium compound are mixed, for example, in a molar ratio of the metal element in the metal oxide to Li in the lithium compound of 1:0.98 to 1:1.1. It should be noted that when mixing the metal oxide and the lithium compound, other metal raw materials may be added as needed.

[0054] The mixture of the metal oxide and the lithium compound is calcined, for example, in an oxygen atmosphere. The mixture may also be calcined through multiple temperature rising processes. The calcining process may include, for example, the following steps: a first temperature rising process of heating from 450°C to 680°C at a temperature rising rate of 1.0°C / min to 5.5°C / min; and a second temperature rising process of heating to a temperature exceeding 680°C at a temperature rising rate of 0.1°C / min to 3.5°C / min. The maximum reaching temperature of the calcining process may be set to 700°C to 850°C, and may be maintained at this temperature for 1 hour to 10 hours.

[0055] Next, the calcined product (lithium-containing transition metal composite oxide) is washed with water and dehydrated to obtain a cake-like composition. The residual alkali component is removed by this washing process. The washing and dehydration can be carried out using existing known methods. Next, the cake-like composition is dried to obtain a powdery composition. The drying process can also be carried out under a vacuum atmosphere. An example of drying conditions is at a temperature of 150°C to 400°C for 0.5 hours to 15 hours.

[0056] The sulfonic acid compound is added, for example, to the cake-like composition obtained in the washing step or the powder-like composition obtained in the drying step. At this time, a sulfonic acid solution may be added instead of the sulfonic acid compound or together with the sulfonic acid compound. Thus, a positive electrode active material having a sulfonic acid compound attached to the surface of particles of the lithium-containing transition metal composite oxide can be obtained. The sulfonic acid compound may also be added as an aqueous dispersion. In addition, the sulfonic acid solution is preferably an aqueous solution of sulfonic acid. The concentration of sulfonic acid in the sulfonic acid solution is, for example, 0.5% by mass to 40% by mass.

[0057] Note that, since a certain amount of lithium compound remains in the cake-like composition, by adding a sulfonic acid solution to the cake-like composition, Li dissolved in water in the cake reacts with the sulfonic acid to obtain lithium sulfonate.

[0058] [negative electrode]

[0059] The negative electrode 12 has a negative electrode core 40 and a negative electrode mixture layer 41 formed on the surface of the negative electrode core 40. The negative electrode mixture layer 41 is preferably provided on both sides of the negative electrode core 40. In addition, the thickness of the negative electrode core 40 is preferably 5 μm to 12 μm. By setting the thickness of the negative electrode core 40 within this range, it is easy to control the 1% compressive strength of the negative electrode core 40 within the target range. The thickness of the negative electrode mixture layer 41 is preferably 50 μm to 150 μm on one side of the negative electrode core 40, for example. The negative electrode 12 can be made, for example, by applying a negative electrode mixture slurry containing a negative electrode active material and a binder on the surface of the negative electrode core 40, drying the coating, and then compressing it to form the negative electrode mixture layer 41 on both sides of the negative electrode core 40, thereby making it.

[0060] The negative electrode core 40 may be made of a foil of a metal that is stable within the potential range of the negative electrode, a film in which the metal is arranged on the surface, etc., but from the viewpoint of improving the cycle characteristics, copper or a copper alloy is preferably used. The negative electrode core 40 made of copper or a copper alloy is stable within the potential range of the negative electrode 12. In addition, when copper or a copper alloy is used, it is easy to control the 1% compressive strength of the negative electrode core 40 within the target range. The copper alloy contains copper as the main component, and the content of copper is preferably 90 mol% or more relative to the total molar number of elements constituting the alloy.

[0061] The 1% compressive strength of the negative electrode core 40 is increased by reducing the crystal grain size of the material of the negative electrode core 40. For example, the crystal grain size of copper as the negative electrode core 40 is preferably 0.2 μm to 2 μm. If the crystal grain size of copper as the negative electrode core 40 is within this range, it is easy to set the 1% compressive strength of the negative electrode core 40 to 300 MPa or more. The crystal grain size can be measured using SEM-EBSD (electron backscatter diffraction method) or the like.

[0062] The 1% compressive strength of the negative electrode core 40 is 300 MPa or more. By setting the 1% compressive strength of the negative electrode core 40 to 300 MPa or more, even if the charge and discharge depth increases due to the presence of the sulfonic acid compound on the particle surface of the positive electrode active material, the volume change of the negative electrode mixture layer 41 during charge and discharge can be suppressed. As a result, even if charge and discharge are repeated, the conductive path between the negative electrode active materials in the negative electrode mixture layer 41 is not lost, and the cycle characteristics of the non-aqueous electrolyte secondary battery 10 can be improved. In addition, from the viewpoint of further improving the cycle characteristics, the 1% compressive strength of the negative electrode core 40 is more preferably 400 MPa or more.

[0063] In the non-aqueous electrolyte secondary battery 10 using a sulfonic acid compound in the positive electrode 11, the cycle characteristics change significantly at the 1% compressive strength of the negative electrode core 40 of 300 MPa. That is, when the 1% compressive strength of the negative electrode core 40 is 300 MPa or more, the cycle characteristics are greatly improved, but when the 1% compressive strength of the negative electrode core 40 is less than 300 MPa, the cycle characteristics are reduced. This is believed to be because the magnitude of the volume change in the negative electrode mixture layer 41 during charge and discharge changes at the 1% compressive strength of the negative electrode core 40 of 300 MPa.

[0064] From the viewpoint of improving the cycle characteristics, the 1% compressive strength of the negative electrode core 40 may be 300 MPa or more. When the 1% compressive strength of the negative electrode core 40 is too high, the possibility of the negative electrode core 40 breaking during battery assembly increases. Therefore, the 1% compressive strength of the negative electrode core 40 is preferably 700 MPa or less, and more preferably 650 MPa or less. Therefore, an example of a suitable range of the 1% compressive strength of the negative electrode core 40 is 300 to 700 MPa, and more preferably 300 to 650 MPa. In the case where the cycle characteristics are particularly important, the 1% compressive strength of the negative electrode core 40 may also be 400 to 700 MPa. If the 1% compressive strength of the negative electrode core 40 is within this range, it is easy to achieve both high capacity and excellent cycle characteristics.

[0065] The 1% compressive strength of the negative electrode core 40 is a compressive strength (1%) measured by the metal material tensile test method of JIS Z 2241. Figure 2 Schematic diagram showing the relationship between strain and stress when a tensile test is performed on the negative electrode core 40. The 1% compressive strength is the value of stress when the strain is 1%. The 1% compressive strength of the negative electrode core 40 can be adjusted by, for example, the thickness of the negative electrode core 40 and the crystal grain size of the material of the negative electrode core 40.

[0066] The elongation at break of the negative electrode core 40 is preferably 12% or less, and more preferably 10% or less. By setting the elongation at break of the negative electrode core 40 to 12% or less, the volume change of the negative electrode mixture layer 41 during charge and discharge can be suppressed, and the cycle characteristics can be improved. In addition, when the elongation at break of the negative electrode core 40 is less than 2%, the possibility of the negative electrode core 40 breaking during battery assembly increases. Therefore, an example of a suitable range of the elongation at break of the negative electrode core 40 is 2 to 12%, and more preferably 2 to 10%.

[0067] The discharge capacity CA (mAh / g) of the negative electrode 12, the thickness CT (μm) of the negative electrode core 40, and the 1% compressive strength CM (N / mm 2 ) preferably satisfies the relationship CA / (CM×CT)<0.25, and more preferably satisfies the relationship CA / (CM×CT)<0.20. By satisfying CA / (CM×CT)<0.25, the volume change of the negative electrode mixture layer 41 during charge and discharge can be suppressed, and the cycle characteristics are improved.

[0068] The binder contained in the negative electrode mixture layer 41 may be fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., as in the case of the positive electrode 11, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode mixture layer 41 preferably contains CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, it is suitable to use SBR in combination with CMC or its salt, PAA or its salt. The content of the binder is, for example, 0.1 to 5% by mass relative to the mass of the negative electrode mixture layer 41. It should be noted that the negative electrode mixture layer 41 may also contain a conductive agent such as CNT.

[0069] The negative electrode mixture layer 41 preferably includes a carbon material and a silicon-containing material as negative electrode active materials. By using a carbon material and a silicon-containing material in combination, it is easy to take into account both high capacity and excellent cycle characteristics. The negative electrode composite material layer 41, for example, substantially only includes a carbon material and a silicon-containing material as negative electrode active materials. The content of the carbon material is preferably higher than the content of the silicon-containing material.

[0070] From the viewpoint of improving the cycle characteristics, the content of the silicon-containing material is preferably less than 20% by mass of the total mass of the negative electrode active material, and more preferably less than 15% by mass. It should be noted that in the non-aqueous electrolyte secondary battery 10 to which a sulfonic acid compound is added to the positive electrode 11, there is a tendency for the cycle characteristics to decrease when there is no silicon-containing material at all. In addition, from the viewpoint of high capacity, the content of the silicon-containing material is preferably more than 5% by mass. Therefore, an example of a suitable range of the content of the silicon-containing material is 5 to 20% by mass of the total mass of the negative electrode active material, and more preferably 5 to 15% by mass.

[0071] The carbon material that functions as the negative electrode active material is, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon. Among them, artificial graphite such as massive artificial graphite (MAG) and graphitized mesocarbon microbeads (MCMB), natural graphite such as flake graphite, massive graphite, and earthy graphite, or a mixture thereof is preferably used. The volume-based D50 of the carbon material is, for example, 1 μm to 30 μm, and preferably 5 μm to 25 μm.

[0072] Soft carbon and hard carbon are classified as amorphous carbon with an underdeveloped graphite crystal structure. More specifically, it refers to a carbon component with a d(002) plane spacing of 0.342 nm or more based on X-ray diffraction. Soft carbon is also called easily graphitizable carbon, which is more easily graphitized by high-temperature treatment compared to hard carbon. Hard carbon is also called difficult-to-graphitize carbon. It should be noted that in the constitution of the present invention, it is not necessary to clearly distinguish between soft carbon and hard carbon. As the negative electrode active material, graphite and at least one amorphous carbon among soft carbon and hard carbon can also be used in combination.

[0073] The silicon-containing material only needs to be a material containing Si. As an example, silicon alloys, silicon compounds, and Si-containing composite materials can be listed. Among them, Si-containing composite materials are preferred. The D50 of the composite material is usually smaller than that of graphite. The volume-based D50 of the composite material is, for example, 1 μm to 15 μm. It should be noted that the silicon-containing material can be used alone or in combination of two or more.

[0074] A suitable silicon-containing material (composite material) is a composite particle containing an ion conduction phase, a Si phase dispersed in the ion conduction phase, and a conductive layer covering the surface of the ion conduction phase. The ion conduction phase is, for example, at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silica phase. The ion conduction phase is a continuous phase composed of a collection of finer particles than the Si phase. The silicide phase is a phase of a compound formed by Si and an element more electropositive than Si. As an example, NiSi, Mg2Si, TiSi2, etc. can be listed. The Si phase is formed by Si being dispersed in fine particulate form. The conductive layer is composed of a material with higher conductivity than the ion conduction phase and forms a good conduction path in the negative electrode binder layer 41.

[0075] An example of a suitable composite material containing Si is a composite particle having an island structure in which Si is dispersed substantially uniformly in an amorphous silica phase and is represented by the general formula SiO x (0 < x ≤ 2). The main component of the silica can also be silicon dioxide. The content ratio (x) of oxygen to Si is, for example, 0.5 ≤ x < 2.0, and preferably 0.8 ≤ x ≤ 1.5.

[0076] Another example of a suitable composite material containing Si is composite particles having a sea-island structure in which Si is substantially uniformly dispersed in the ionic conduction phase in a particulate form. The ionic conduction phase contains, for example, at least one selected from the group consisting of an alkali metal element and a Group II element. Further, the ionic conduction phase may also contain another element M other than the alkali metal element and the Group II element. The element M may also be at least one selected from the group consisting of B, Al, Zr, Nb, Ta, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F, W, and lanthanide elements.

[0077] A suitable ionic conduction phase is a lithium silicate phase containing Li. The lithium silicate phase is, for example, a phase of a composite oxide represented by the general formula Li 2z SiO (2+z) (0 < z < 2). It is preferred that the lithium silicate phase does not contain Li4SiO4 (Z = 2). Li4SiO4 is an unstable compound and reacts with water to show alkalinity. Therefore, it sometimes deteriorates Si, resulting in a decrease in charge-discharge capacity. From the viewpoints of stability, productivity, Li ion conductivity, etc., the lithium silicate phase is preferably mainly composed of Li2SiO3 (Z = 1) or Li2Si2O5 (Z = 1 / 2).

[0078] Another example of a suitable composite material containing Si is composite particles having a sea-island structure in which fine Si is substantially uniformly dispersed in the carbon phase. The carbon phase is preferably an amorphous carbon phase. The carbon phase may also contain a crystalline phase component, but preferably has a large amorphous phase component. The amorphous carbon phase is composed of, for example, a carbon material having an average interplanar spacing of the (002) plane measured by X-ray diffraction exceeding 0.34 nm. The amorphous carbon phase is composed of, for example, particles of amorphous carbon. It should be noted that the composite material containing the carbon phase may or may not have a conductive layer different from the carbon phase.

[0079] The conductive layer formed on the surface of the composite material particles is, for example, a carbon coating film composed of a conductive carbon material. As the conductive carbon material, carbon black such as acetylene black and Ketjen black, graphite, and amorphous carbon with low crystallinity can be used. Considering ensuring conductivity and the diffusibility of Li ions into the particles, the thickness of the conductive layer is preferably 1 nm to 200 nm or 5 nm to 100 nm. The thickness of the conductive layer can be measured by observing the cross section of the composite material using SEM or a transmission electron microscope (TEM).

[0080] [Separator]

[0081] The separator 13 uses a porous sheet with ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, nonwoven fabrics, etc. can be cited. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 can be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aramid resin can be formed on the surface of the separator 13.

[0082] A filler layer containing an inorganic filler may also be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.

[0083] Example

[0084] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.

[0085] <Example 1>

[0086] [Preparation of positive electrode active material]

[0087] The [Ni 0.90 Al 0.05 Mn 0.05 The composite hydroxide represented by ](OH)2 was calcined at 500°C for 8 hours to obtain a metal oxide (Ni 0.90 Al 0.05 Mn 0.05 Next, LiOH and the above metal oxides were mixed in such a way that the molar ratio of Li to the total amount of Ni, Al and Mn was 1.03:1 to obtain a mixture. The mixture was heated under an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3At a flow rate of 2 mL / min and 5 L / min per 1 kg of the mixture, the mixture was fired from room temperature to 650 °C at a heating rate of 2.0 °C / min, and then fired from 650 °C to 780 °C at a heating rate of 0.5 °C / min to obtain a lithium-containing composite oxide (synthesis process). Water was added to the lithium-containing composite oxide such that the slurry concentration became 1500 g / L, stirred for 15 minutes, and filtered to obtain a cake-like composition (washing process). Lithium methanesulfonate in powder form was added to the cake-like composition (addition process). The addition amount of lithium methanesulfonate was 0.1% by mass relative to the total mass of the lithium-containing composite oxide. After the addition process, a drying process was carried out under a vacuum atmosphere at 180 °C for 2 hours to obtain the positive electrode active material of Example 1. It should be noted that it was confirmed by Fourier transform infrared spectroscopy (FT-IR) that lithium sulfonate was present on the surface of the positive electrode active material.

[0088] [Fabrication of Positive Electrode]

[0089] The above positive electrode active material, acetylene black, and polyvinylidene fluoride were mixed at a mass ratio of 98:1:1, and N-methyl-2-pyrrolidone (NMP) was used as a dispersion medium to prepare a positive electrode mixture slurry. Then, the positive electrode mixture slurry was coated on a positive electrode core formed of aluminum foil, the coating film was dried, compressed, and then the positive electrode core was cut into a specified electrode size to obtain a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode core. It should be noted that an exposed portion where the surface of the positive electrode core was exposed was provided on a part of the positive electrode.

[0090] [Fabrication of Negative Electrode]

[0091] Artificial graphite and SiO were mixed at a mass ratio of 94:6 x (0 < x ≤ 2), and it was used as the negative electrode active material. The negative electrode active material, a dispersant of carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), were mixed at a solid component mass ratio of 98:1:1, and water was used as a dispersion medium to prepare a negative electrode mixture slurry. The negative electrode mixture slurry was coated on both sides of a negative electrode core formed of a copper foil with a thickness of 8 μm and a crystal particle size of 0.5 μm. After the coating film was dried, the coating film was calendered using a roller and cut into a specified electrode size to obtain a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode core. It should be noted that an exposed portion where the surface of the negative electrode core was exposed was provided on a part of the negative electrode.

[0092] [Preparation of Non-aqueous Electrolyte]

[0093] In a mixed solvent obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (MEC), and dimethyl carbonate (DMC) at a volume ratio of 3:3:4 (25 °C), LiPF6 was dissolved at a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0094] [Fabrication of test battery cell (non-aqueous electrolyte secondary battery)]

[0095] An aluminum lead is attached to the exposed portion of the positive electrode, a nickel lead is attached to the exposed portion of the negative electrode, and the positive electrode and the negative electrode are spirally wound with a polyolefin separator interposed therebetween to prepare a wound electrode body. The electrode body is housed in an outer can made of an aluminum laminate sheet, the nonaqueous electrolyte is injected, and the opening of the outer can is sealed to obtain a test battery cell.

[0096] [Cycle test]

[0097] For the above test battery cell, at a temperature of 25°C, constant current charging was performed at a constant current of 0.2It until the battery voltage reached 4.2V, and constant voltage charging was performed at 4.2V until the current value reached 0.02It. Then, constant current discharge was performed at a constant current of 0.2It until the battery voltage reached 2.5V. This charge and discharge cycle was regarded as 1 cycle, and repeated 200 cycles. The discharge capacity of the 1st cycle and the discharge capacity of the 200th cycle of the cycle test were obtained, and the capacity retention rate was calculated according to the following formula.

[0098] Capacity retention rate (%) = (discharge capacity at the 200th cycle ÷ discharge capacity at the 1st cycle) × 100

[0099] [Evaluation of 1% compressive strength and elongation at break of negative electrode core]

[0100] After the cycle test, the test battery cell is disassembled and the negative electrode is taken out. According to the metal material tensile test method of JIS Z 2241, the 1% compressive strength (offset method) and elongation at break are measured for the negative electrode core punched into a dumbbell shape using Shimadzu Auto Graph (AG-IS). In addition, the elongation at break of the length of the side in the width direction of the negative electrode before loading into the test battery cell is calculated. The 1% compressive strength of the negative electrode core of Example 1 is 550 MPa, and the elongation at break is 5%.

[0101] <Example 2>

[0102] In the step of adding the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that the amount of lithium methanesulfonate added was 0.3 mass % based on the total mass of the lithium-containing composite oxide.

[0103] <Example 3>

[0104] In the step of adding the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that the amount of lithium methanesulfonate added was 0.5 mass % based on the total mass of the lithium-containing composite oxide.

[0105] <Example 4>

[0106] In the step of adding the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 1.0% by mass, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.

[0107] <Example 5>

[0108] In the step of adding the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 0.5% by mass, and in the production of the negative electrode, the thickness of the negative electrode core was set to 5 μm, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.

[0109] <Example 6>

[0110] In the step of adding the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 0.5% by mass, and in the production of the negative electrode, the strength of the negative electrode core was changed, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.

[0111] <Example 7>

[0112] In the step of adding the positive electrode active material, sodium methanesulfonate was added as the sulfonic acid compound, and its addition amount was set to 0.5% by mass relative to the total mass of the lithium-containing composite oxide, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.

[0113] <Example 8>

[0114] In the step of adding the positive electrode active material, lithium ethanesulfonate was added as the sulfonic acid compound, and its addition amount was set to 0.5% by mass relative to the total mass of the lithium-containing composite oxide, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.

[0115] <Example 9>

[0116] In the step of adding the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 0.5% by mass, and in the production of the negative electrode, artificial graphite and SiO x (0 < x ≤ 2) were mixed at a mass ratio of 85:15, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.

[0117] <Comparative Example 1>

[0118] In the addition step of the positive electrode active material, a sulfonic acid compound was not added. In the production of the negative electrode, the strength of the negative electrode core was changed, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was performed.

[0119] <Comparative Example 2>

[0120] In the addition step of the positive electrode active material, a sulfonic acid compound was not added, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was performed.

[0121] <Comparative Example 3>

[0122] In the addition step of the positive electrode active material, lithium succinate was added, and the addition amount thereof was set to 0.5% by mass relative to the total mass of the lithium-containing composite oxide. A test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was performed.

[0123] <Comparative Example 4>

[0124] In the addition step of the positive electrode active material, lithium oxalate was added, and the addition amount thereof was set to 0.5% by mass relative to the total mass of the lithium-containing composite oxide. A test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was performed.

[0125] <Comparative Example 5>

[0126] In the addition step of the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 0.5% by mass. In the production of the negative electrode, the strength of the negative electrode core was changed, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was performed.

[0127] <Comparative Example 6>

[0128] In the addition step of the positive electrode active material, a sulfonic acid compound was not added. In the production of the negative electrode, artificial graphite and SiO were mixed at a mass ratio of 85:15 x (0 < x ≤ 2), and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was performed.

[0129] <Comparative Example 7>

[0130] In the addition step of the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 0.5% by mass. In the production of the negative electrode, artificial graphite and SiO were mixed at a mass ratio of 85:15 x (0 < x ≤ 2), the strength of the negative electrode core was changed, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was performed.

[0131] The capacity retention rates of the test battery cells of the embodiments and comparative examples after 200 cycles are shown in Tables 1 and 2, respectively. In addition, Tables 1 and 2 also show the discharge capacity CA of the negative electrode, the characteristics of the negative electrode core (thickness CT, 1% compressive strength CM, elongation at break), and the value of CA / (CM×CT). It should be noted that the capacity retention rate after 200 cycles in Table 1 is a relative value when the capacity retention rate of the test battery cell of Comparative Example 1 is set to 100, and the capacity retention rate after 200 cycles in Table 2 is a relative value when the capacity retention rate of the test battery cell of Comparative Example 6 is set to 100. A larger value indicates a better cycle characteristic.

[0132] [Table 1]

[0133]

[0134] [Table 2]

[0135]

[0136] As shown in Table 1, the test battery cells of Examples 1 to 8, which used a sulfonic acid compound in the positive electrode and a negative electrode core having a 1% compressive strength of 300 MPa or more in the negative electrode, all showed improved capacity retention after 200 cycles compared with the test battery cells of Comparative Examples 1 to 5. In addition, the test battery cell of Comparative Example 2, which did not use a sulfonic acid compound in the positive electrode and used a negative electrode core having a 1% compressive strength of 550 MPa in the negative electrode, showed poor cycle characteristics compared with the test battery cells of Examples 1 to 8. In addition, the test battery cell of Comparative Example 5, which used a sulfonic acid compound in the positive electrode and used a negative electrode core having a 1% compressive strength of 200 MPa in the negative electrode, showed poor cycle characteristics compared with the test battery cells of Examples 1 to 8.

[0137] As shown in Table 2, when a negative electrode active material having a silicon content of 15 mass % is used in the negative electrode, the capacity retention rate after 200 cycles is also improved by using a sulfonic acid compound in the positive electrode and using a negative electrode core having a compressive strength of 300 MPa or more in the negative electrode.

[0138] From the above results, when a negative electrode core having a 1% compressive strength of 300 MPa or more is used in the negative electrode, the cycle characteristics are greatly improved by using a sulfonic acid compound in the positive electrode. On the other hand, when a negative electrode core having a 1% compressive strength of less than 300 MPa is used in the negative electrode, it is difficult to improve the cycle characteristics even if a sulfonic acid compound is used in the positive electrode.

[0139] The present disclosure is further described by the following embodiments.

[0140] Configuration 1: A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the positive electrode comprises a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of particles of the composite oxide, wherein the sulfonic acid compound is a compound represented by the above formula (I), and the negative electrode comprises a negative electrode core and a negative electrode mixture layer formed on the surface of the negative electrode core, wherein the 1% compressive strength of the negative electrode core is greater than 300 MPa.

[0141] Configuration 2: The nonaqueous electrolyte secondary battery according to Configuration 1, wherein the sulfonic acid compound is present in an amount of 0.1 mass % or more and 1.0 mass % or less relative to the mass of the lithium-containing transition metal composite oxide.

[0142] Configuration 3: The nonaqueous electrolyte secondary battery according to Configuration 1 or 2, wherein A in formula (I) is Li or Na.

[0143] Configuration 4: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein R in formula (I) is an alkyl group having 3 or less carbon atoms.

[0144] Configuration 5: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein the lithium-containing transition metal composite oxide has a layered rock salt structure.

[0145] Configuration 6: A non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 5, wherein the discharge capacity CA (mAh / g) of the negative electrode, the thickness CT (μm) of the negative electrode core, and the 1% compressive strength CM (N / mm 2 ) satisfies the relationship CA / (CM×CT)<0.25.

[0146] Configuration 7: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 6, wherein the negative electrode core has a breaking elongation of 2% or more and 9% or less in a tensile test.

[0147] Configuration 8: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 7, wherein the negative electrode core is copper or a copper alloy having a crystal grain size of 0.2 μm or more and 2.0 μm or less.

[0148] Configuration 9: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 8, wherein the thickness of the negative electrode core is 5 μm or more and 12 μm or less.

[0149] Configuration 10: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 9, wherein the negative electrode mixture layer contains a carbon material and a silicon-containing material as negative electrode active materials.

[0150] Configuration 11: The nonaqueous electrolyte secondary battery according to Configuration 10, wherein the carbon material is at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon.

[0151] Configuration 12: The nonaqueous electrolyte secondary battery according to Configuration 10 or 11, wherein the content of the silicon-containing material is 5 mass % or more and 20 mass % or less of the total mass of the negative electrode active material.

[0152] Configuration 13: The nonaqueous electrolyte secondary battery according to any one of Configurations 10 to 12, wherein the silicon-containing material includes an ion conductive phase, a Si phase dispersed in the ion conductive phase, and a conductive layer covering a surface of the ion conductive phase.

[0153] Configuration 14: The nonaqueous electrolyte secondary battery according to Configuration 13, wherein the ion conductive phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase.

[0154] Configuration 15: The nonaqueous electrolyte secondary battery according to Configuration 13 or 14, wherein the ion conductive phase contains at least one selected from the group consisting of alkali metal elements and Group II elements.

[0155] Configuration 16: A non-aqueous electrolyte secondary battery according to Configuration 15, wherein the ion conductive phase further comprises an element M, and the element M is at least one selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.

[0156] Description of Reference Numerals

[0157] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 positive electrode core body, 31 positive electrode mixture layer, 40 negative electrode core body, 41 negative electrode mixture layer.

Claims

1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode comprises a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles. The sulfonic acid compound is a compound represented by formula (I), A is a Group 1 or Group 2 element, R is a hydrocarbon group, n is 1 or 2, The negative electrode comprises a negative electrode core and a negative electrode mixture layer formed on a surface of the negative electrode core. The 1% compressive strength of the negative electrode core is above 300 MPa.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The sulfonic acid compound is present in an amount of 0.1 mass % or more and 1.0 mass % or less relative to the mass of the lithium-containing transition metal composite oxide.

3. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: A in formula (I) is Li or Na.

4. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: R in the formula (I) is an alkyl group having 3 or less carbon atoms.

5. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The lithium-containing transition metal composite oxide has a layered rock salt structure.

6. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The discharge capacity CA (mAh / g) of the negative electrode, the thickness CT (μm) of the negative electrode core, and the 1% compressive strength CM (N / mm 2 ) satisfies the relationship CA / (CM×CT)<0.

25.

7. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The negative electrode core has a breaking elongation of 2% or more and 12% or less during a tensile test.

8. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The negative electrode core is copper or a copper alloy having a crystal grain size of 0.2 μm or more and 2.0 μm or less.

9. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The thickness of the negative electrode core is greater than or equal to 5 μm and less than or equal to 12 μm.

10. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The negative electrode mixture layer contains a carbon material and a silicon-containing material as negative electrode active materials.

11. The nonaqueous electrolyte secondary battery according to claim 10, wherein The carbon material is at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon.

12. The nonaqueous electrolyte secondary battery according to claim 10, wherein The content of the silicon-containing material is 5 mass % or more and 20 mass % or less of the total mass of the negative electrode active material.

13. The nonaqueous electrolyte secondary battery according to claim 10, wherein The silicon-containing material includes an ion-conducting phase, a Si phase dispersed in the ion-conducting phase, and a conductive layer covering a surface of the ion-conducting phase.

14. The nonaqueous electrolyte secondary battery according to claim 13, wherein The ion-conducting phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase.

15. The nonaqueous electrolyte secondary battery according to claim 13, wherein The ion conductive phase includes at least one selected from the group consisting of alkali metal elements and Group II elements.

16. The nonaqueous electrolyte secondary battery according to claim 15, wherein The ion conductive phase further contains an element M, and the element M is at least one selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.

Citation Information

Patent Citations

  • Lithium titanate powder for power storage device electrode, active substance material, and power storage device using the active substance material

    JP2018006164A